2018
DOI: 10.1371/journal.pone.0201471
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of components from root exudates of Welsh onion against root knot nematodes

Abstract: Root-knot nematodes (RKNs; Meloidogyne spp.) are obligate endoparasites that infect many crops and cause severe yield losses. In this research, we studied the effect of Welsh onion, grown as a companion plant, on the resistance of cucumber plants to RKN infection and analyzed the most abundant components of Welsh onion root exudates. The results showed that, when grown with Welsh onion as a companion plant, cucumber roots had 77.0% fewer root knots and egg masses than the control cucumber roots. Welsh onion ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The second most effective treatment in reducing root-knot nematodes, Meloidogyne spp., the number was 4rows with 80 kg nitrogen in two successive seasons. Results are in agreement with (Li et al, 2018) who showed that, when cucumber has grown with welsh onion as a companion plant, cucumber roots reduced root galls and egg-masses than the control cucumber roots. The same trend was noticed by Abdel-Baset (2007) who reported that intercropping onion with green bean reduced the root-knot nematode, M. incongita reproduction in the greenhouse.…”
Section: Interaction Effect Between Onion Plant Density and Slow-relesupporting
confidence: 92%
See 2 more Smart Citations
“…The second most effective treatment in reducing root-knot nematodes, Meloidogyne spp., the number was 4rows with 80 kg nitrogen in two successive seasons. Results are in agreement with (Li et al, 2018) who showed that, when cucumber has grown with welsh onion as a companion plant, cucumber roots reduced root galls and egg-masses than the control cucumber roots. The same trend was noticed by Abdel-Baset (2007) who reported that intercropping onion with green bean reduced the root-knot nematode, M. incongita reproduction in the greenhouse.…”
Section: Interaction Effect Between Onion Plant Density and Slow-relesupporting
confidence: 92%
“…Reducing nematode populations may due to onion root exudates consist of a variety of compounds, for example, hexahydro-3-(2methylpropyl)-pyrrolo[1,2-a]pyrazine-1,4-dione, Nformyl-tyramine, dibutyl phthalate or hexahydro-3-(phenylmethyl)-pyrrolo[1,2-a] pyrazine-1,4-dione, which involved in inhibition of root-knot nematodes activity and egg hatchability. The exudate compounds may likely have a complex interrelationship on resistance against root-knot nematodes (Li et al, 2018).…”
Section: Interaction Effect Between Onion Plant Density and Slow-relementioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the root exudates under field conditions stimulated the hatch of the J2, so that the bioassay also measured those nematodes present in the soil. Compounds released by plants into the soil could attract nematodes to the roots [41]. Such differences in the ratio of J2/eggs between the three types of radish bioassay were not observed at Jeinsen under the oilseed radish treatment.…”
Section: Discussionmentioning
confidence: 82%
“…The nematode assay was conducted following Kim et al (2020). We focused on number of offspring as a target parameter since previous studies have pointed out that the extracts from plant litters can inhibit the hatching of embryos (Meyer et al, 2013;Li et al, 2018). Briefly, we added 0.3 g of each test soil into each well of a 24-well plate (n 6), moisturized with 82 μL of K-medium (80% of WHC).…”
Section: Nematode Assaymentioning
confidence: 99%